2013
DOI: 10.1080/11250003.2013.859309
|View full text |Cite
|
Sign up to set email alerts
|

Blood and seminal plasma enzyme values of Persian sturgeon,Acipenser persicus(Chordata: Osteichthyes)

Abstract: An important aspect in the management and protection of endangered species from extinction is the determination of normal physiological values, including the blood and seminal plasma properties. This study was undertaken to establish a reference range for six important blood and seminal plasma enzymes. Samples of 20 Acipenser persicus Borodin, 1897 (10 female and 10 male) were analyzed. The reference ranges for the total samples and also for each sex were determined. The activities of measured enzymes in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The analysis of blood parameters is one of the most valuable modern methods because it has been shown that their physiological values are species‐specific and sex‐dependent (Anver, ; Aramli et al., ). Analysis of electrolyte (Na + , K + and Cl −) of blood plasma indicated that the Na + and Cl ‐ levels were lower than the values in other sturgeon, such as A. stellatus and A .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of blood parameters is one of the most valuable modern methods because it has been shown that their physiological values are species‐specific and sex‐dependent (Anver, ; Aramli et al., ). Analysis of electrolyte (Na + , K + and Cl −) of blood plasma indicated that the Na + and Cl ‐ levels were lower than the values in other sturgeon, such as A. stellatus and A .…”
Section: Resultsmentioning
confidence: 99%